Transformasi Manajemen Keuangan Sekolah di Era Digital: Kajian Literatur terhadap Efektivitas, Transparansi, dan Akuntabilitas Pengelolaan Dana Pendidikan di Indonesia: Penelitian - Lena Rusmiyati; Ridwan Abdullah; Siti Zulaikha; Muh. Takdir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to conduct a systematic review of various scientific literature that discusses the application of information technology in strengthening financial governance in educational institutions in Indonesia. The method used is a literature study with a qualitative descriptive approach, which analyzes 15 national and international scientific articles published between 2019 and 2025. The results of the study show that the application of digital financial systems, such as ARKAS, SIMUTU, and blockchain technology, has been proven to increase efficiency in the budget planning and reporting process, strengthen public transparency, and encourage accountability based on evaluation and community participation. However, digitalization also faces various challenges, such as limited infrastructure, digital literacy of financial managers, and data security. Therefore, collaboration between the government, schools, and the private sector, as well as adaptive regulations are needed to build an inclusive, safe, and sustainable education financial system. This study recommends strengthening human resource capacity and integrating digital systems into school financial policies as the main strategy to support the quality of national education.